Estymacja przedziałowa, jako wymiar wartości niematerialnej: Interval estimation as the dimension of intangible value - Kowalska-Napora, Ewa (Management and Administration Journal, 2021)
Written by the author, the system of creating values equally includes individual and integrated chains of values of individual links, which on the one hand have to be flexible and respond quickly to changes in demand, and at the same time create a value on both the local markets, as well as globally. This paper analyzes the impact of behaviour patterns of links with the value and quality created in the network of cooperating links. With its issues the paper touches upon the aspects of quality management on macro-scale and interprets the phenomena of quality influence on the added value in the network. The research novelty here is the constitution of the quality criterion as intangible and subjected values. Written by the author, while determining ways to solve a problem you need to define the problem, identify the need for changeas well as its solution, defining alternatives. The paper touches upon the problems of identifying the function of an object, selecting its sets and cancelling such characteristics – so as to categorize properly the scope of a decision. The novelty of the analysis is selecting the estimated value and its impact on the extent of target optimization within the sensitivity area.